In the Woods and on the Waves: Attentive Acoustics and Active Instruments in The Mysteries of Udolpho - Wheeler, Joel (Lumen, 2024)
The 21st century has brought new attention to the use of music in Ann Radcliffe’s novel, The Mysteries of Udolpho (1794). To date, much of this work focuses on how unknown music evokes the fearful elements of the Gothic. However, reducing key sonic scenes to a sense of fear neglects Emily’s often positive relationship to sound. A re-examination of this seemingly “haunted” music reveals it to be a more ambiguous vessel for the protagonist Emily’s creative projections. Current scholarship also omits full analysis of Emily’s lute, both in the setting of the novel and in Radcliffe’s era. Emily’s lute performances, considered in their historic context and read as an act of resistance, free her from a typical heroine’s depiction of inert interiority. In both cases, considering how Emily creatively listens to and actively performs music reveals productive new tones within the novel.